2020
DOI: 10.1101/2020.05.06.080564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detailed temporal dissection of an enhancer cluster reveals two distinct roles for individual elements

Abstract: 14Many genes are regulated by multiple enhancers that often simultaneously activate their target gene. Yet, 15how individual enhancers collaborate to activate transcription is not well understood. Here, we dissect the 16 functions and interdependencies of five enhancer elements that form a previously identified enhancer 17 cluster and activate the Fgf5 locus during exit from naïve murine pluripotency. Four elements are located 18 downstream of the Fgf5 gene and form a super-enhancer. Each of these elements con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The finding that interacting with more than three enhancers provided little additional increase in expression may also provide insights into super-enhancers. Although it is clear at least some constituent parts of super-enhancers act in a simple additive manner 19 , this result suggests additivity is not the entire picture, and may be consistent with enhancers having distinct mechanistic roles or heirachy 58,59 . Therefore, high levels of transcription driven by multiple enhancers, and/or the effect of superenhancers could be as a result of combining multiple enhancer functions.…”
Section: Discussionmentioning
confidence: 88%
“…The finding that interacting with more than three enhancers provided little additional increase in expression may also provide insights into super-enhancers. Although it is clear at least some constituent parts of super-enhancers act in a simple additive manner 19 , this result suggests additivity is not the entire picture, and may be consistent with enhancers having distinct mechanistic roles or heirachy 58,59 . Therefore, high levels of transcription driven by multiple enhancers, and/or the effect of superenhancers could be as a result of combining multiple enhancer functions.…”
Section: Discussionmentioning
confidence: 88%
“…Genomic studies of chromatin marks have revealed hundreds of thousands candidate CREs in the human genome but with very little quantitative information regarding how CREs contribute to gene regulation 35, 36 . Using CRISPRpath, we can systematically classify enhancers based on their effect sizes on transcription.…”
Section: Discussionmentioning
confidence: 99%
“…This observation can be explained by the fact that enhancer-like promoters will not only form chromatin loops with their distal target genes, but also with CREs for controlling the expression of their own genes. Genomic studies of chromatin marks have revealed hundreds of thousands candidate CREs in the human genome but with very little quantitative information regarding how CREs contribute to gene regulation (36,37). Using CRISPRpath, we can systematically classify enhancers based on their effect sizes on transcription.…”
Section: Discussionmentioning
confidence: 99%
“…SEs also exhibit relatively higher levels of H3K27Ac and are larger in size overall compared with enhancers ( Parker et al, 2013 ; Pulakanti et al, 2013 ). Several studies show that SE differ from classical enhancers due to their stronger ability to drive gene expression than classical enhancers ( Hnisz et al, 2015 ; Huang et al, 2016 ; Shin et al, 2016 ; Thomas et al, 2021 ). SEs are also highly cell-type specific and are often found near key lineage determining genes, implying they are critical to the establishment and/or maintenance of cell identity.…”
Section: Enhancersmentioning
confidence: 99%